Pengaruh Kegiatan Mendongeng dengan Media Wayang terhadap Perkembangan Sosial Emosional pada Anak Usia 5-6 Tahun di TK Tatuka Kesuma Palembang - Azah Nadya Balqista; Muhtarom Muhtarom; Izza Fitri; Mardiah Astuti; Aida Imtihana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the impact of storytelling activities using wayang media on the social and emotional development of children aged 5-6 years at Tatuka Kesuma Kindergarten, Palembang. The method applied in this study is an experimental method, which focuses on the analysis of cause-and-effect relationships between the variables studied. The research design used is a One Group Pretest Posttest Design, which allows researchers to measure changes that occur before and after the intervention. The population that became the subject of this study were 11 children in grade B at Tatuka Kesuma Kindergarten, Palembang. The selection of this subject was based on initial observations that indicated problems in the social and emotional aspects of children at the school. The observations were aimed at understanding more deeply the social and emotional conditions of children in grade B, as well as to assess the effect of storytelling activities using wayang media. The results of the study showed a significant increase in the social and emotional development of children aged 5-6 years after participating in storytelling activities using wayang media. This increase included aspects such as the ability to interact, empathy, and emotional management. Thus, it can be concluded that storytelling activities using wayang media have a positive influence on the social and emotional development of children at Tatuka Kesuma Kindergarten, Palembang. This study provides evidence that creative and interactive storytelling methods can be an effective tool in supporting the social and emotional development of early childhood, and highlights the importance of using engaging media in the learning process. Furthermore, the results of this study can also serve as a reference for educators and parents to pay more attention to teaching methods that can improve children's social and emotional skills.